27-GAUGE SUTURELESS INTRASCLERAL FIXATION OF INTRAOCULAR LENSES WITH HAPTIC FLANGING: Short-Term Clinical Outcomes and a Disinsertion Force Study. Issue 11 (November 2019) - Stem, Maxwell S.; Wa, Christianne A.; Todorich, Bozho; Woodward, Maria A.; Walsh, Mark K.; Wolfe, Jeremy D.
Abstract : Purpose: To determine whether haptic flanging during 27-gauge sutureless intrascleral fixation of intraocular lenses (IOLs) increases IOL stability and to report the short-term clinical outcomes of sutureless intrascleral surgery using 27-gauge trocar cannulas with haptic flanging. Methods: Retrospective surgical case series using live and cadaveric human eyes. Results: In the cadaveric experiment using five eyes, flanged haptics required more force to dislocate the IOL compared with unflanged haptics (14 ± 4 vs. 3 ± 1 g, P = 0.03). The clinical series included 52 eyes from 52 patients. The average age at the time of surgery was 73 ± 14 years, with a mean follow-up of 27 ± 19 weeks. The most common indication for surgery was IOL dislocation/subluxation (n = 43, 83%). Mean visual acuity improved from 20/140 preoperatively to 20/50 at postoperative Month 1 ( P < 0.001). The most common postoperative issue was intraocular pressure elevation (n = 12, 23%). Two patients (4%) needed a reoperation for IOL dislocation. Conclusion: Haptic flanging during 27-gauge sutureless intrascleral surgery creates a more stable scleral-fixated IOL compared with the traditional unflanged technique based on a cadaveric human eye study. In addition, this variation of sutureless intrascleral surgery seems safe and effective for patients who require secondary IOLs. Abstract : Using cadaveric eyes, the authors demonstrate that flanging the haptics of a sutureless intrascleral intraocular lens creates a more stable scleral-fixated intraocular lens compared with the traditional unflanged technique. In addition, this variation of sutureless intrascleral surgery seems safe and effective for patients who require secondary intraocular lenses.